A Case of Isolated Central Nervous System Vasculitis in an Elderly Patient - Clara Bartolaminelli; Gian Paolo Anzola; Matteo Filippini; Gianluca Boari (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2017)
A 83 year old Italian woman, with unremarkable family history, was admitted in 2013 to a Neurology Ward for lumbar pain and progressive motor impairment of right lower limb. The only remarkable event in her past history had been a clinical diagnosis of Rheumatoid Arthritis (RA) 20 years earlier, not confirmed by laboratory tests and radiological imaging. The neurological examination showed an isolated mild right lower limb paresis, 4/5 on the MRC scale (medical research council muscle scale), no sensory defi cit and preserved symmetrical tendon refl exes. Brain MRI (magnetic resonance imaging) showed multiple patchy lesions, hyperintense on T2 and FLAIR, in the subcortical white matter and in the pons. CSF (cerebrospinal fluid) examination showed no abnormality and oligoclonal bands were absent. MRI of the spinal cord showed enlargement from D6 to D11. The ventral aspect was diffusely hyperintense on D2, with a nonhomogeneous enhancement. A transverse myelitis was hypothesized.